System Economic Costs of Antibiotic Use Elimination in the US Beef Supply Chain - Kaniyamattam, Karun; Tauer, Loren W.; Gröhn, Yrjö T. (Frontiers in Veterinary Science, 2021)
There is consumer pressure on the U.S. beef industry to minimize antibiotic use (ABU) in order to aid in the global antimicrobial resistance mitigation efforts. Our objective was to estimate the economic costs of ABU constraints in a conceptual U.S. integrated beef supply chain (IBSC) to aid the beef industry in mitigating the risk of antimicrobial resistance, by reducing their ABU. An IBSC network model was developed and differentiated into 37 different nodes of production. Each node could only raise a specific type of animals, differentiated based on the production technique and animal health status. The cost as well as the weight gain coefficient was estimated for each node, using an IBSC cost of production model. Linear programming solutions to this network model provided the least cost path of beef supply through the system, under various ABU constraints. The cost as well as weight gain coefficient of the 37 nodes, and the initial supply of 28.5 million calves weighing 0.65 million metric tons, and the final demand of 16.14 million metric tons of slaughter ready cattle were used as inputs to the 3 different linear programming models, with different ABU constraints. Our first model which placed no constraint on ABU, estimated the minimum economic cost to meet the final beef demand as $38.2 billion. The optimal solution was to use only the high health calves for production. Because low health calves occur in the beef system, our second model required all the calves irrespective of their health status to be used, which increased the system cost to $41.5 billion. Thus, the value of only producing high health status calves is $3.3 billion. Our third model, which restricted feedlots from using antibiotics even with low health calves, incurred a total cost of $41.9 billion for antibiotic free beef production. We concluded that the additional cost of $367 million for implementing antibiotic free beef production is relatively low; approximately 0.87% of the minimum cost incurred for the conventional beef supply chain (model 2 cost of $41.5 billion). However, a much higher cost savings is obtained by producing only high health status calves.